Perancangan Mesin Pengaduk Media Tanam Jamur Tiram Dengan Pendekatan Metode NIDA - Falah, Muhamad Miftakhul; Izzhati, Dwi Nurul (JURMATIS (Jurnal Manajemen Teknologi dan Teknik Industri), 2026)
Indonesia has significant agrarian potential, with oyster mushrooms as a high-value economic and nutritious commodity. Production is supported by 25.1 million farming households and 17.2 million smallholder farmers, yielding 43.36 million kg annually. This study aims to design a log bag production machine capable of producing >38 kg per batch, equipped with a 6.5 HP motor and a 200 L drum, with a total manufacturing cost of <IDR 3,800,000 and a potential profit margin >18%. A quantitative case study methodology was applied to the "Jamur Widodo" enterprise, using NIDA methods and Activity Based Costing (ABC) to identify and allocate production costs. The designed machine, with a capacity of >40 kg per batch, a 5.5–6.5 HP motor, 200 L drum, specialized blades, 4×4 cm hollow frame, and speed reducer, successfully met user requirements (voice of customer). The machine proved efficient, ergonomic, and stable in mixing growing media. A total production cost of IDR 3,701,000 allows a selling price of IDR 4,441,200 with a 20% margin, demonstrating economic feasibility for small-scale production. These findings contribute significantly to improving efficiency, reducing operational costs, and enhancing oyster mushroom production capacity economically.